No association of DNM3 with age of onset in Asian Parkinson's disease - Foo, Jia Nee (2020)
Background: Genetic variability in DNM3 have been shown to modify age of onset of Parkinson’s disease (PD) among LRRK2 Gly2019Ser carriers in North African Arab-Berber populations. In Asian populations, the Gly2019Ser mutation is rare or absent but two other LRRK2 variants Gly2385Arg and Arg1628PPro increase PD risk. We aim to determine if the DNM3 locus is associated with age of PD onset in both carriers and non-carriers of LRRK2 risk variants in Asians. Methods: We analyzed the association of DNM3 rs2421947 genotypes with age of PD onset in 3,645 Chinese samples, of which 369 carry at least one of two Asian LRRK2 risk variants. Results: DNM3 rs2421947 genotypes were not associated with PD age of onset in Chinese samples. We observed no heterogeneity in the effect of rs2421947 between the Asian LRRK2 risk variant carriers and non-carriers. Conclusions: DNM3 rs2421947 is not associated with age of PD onset in LRRK2 risk variant carriers and non-carriers in Chinese. Further studies in other Asian populations will be of interest.